2011
DOI: 10.1002/app.34464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of filler type on the nonisothermal crystallization kinetics of poly(butylene terephthalate) (PBT) composites

Abstract: In this study, melt-crystallization behaviors of poly(butylene terephthalate) (PBT) composites including different types of inorganic fillers were investigated. Composite samples having 5 wt % of fillers were prepared by melt processing in a twin screw extruder using commercial grades of calcite (CA), halloysite (HL), and organomontmorillonite (OM) as filler. Depending on the filler type and geometry, crystallization kinetics of the samples was studied by differential scanning calorimetry (DSC) methods. Effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The inter-relationship between these two parameters governs the activation energy for crystallization, DE. Following the isokinetic method of Augis-Bennet, DE values were evaluated [56][57][58][59]: where T 0 is the initial reference temperature from the melt state, T p the crystallization peak temperature, R g the universal gas constant (R g = 8.314 J mol -1 K -1 ), and R is the cooling rate. The activation energy was calculated from the slopes, of the plots, Fig.…”
Section: Activation Energy Of Crystallizationmentioning
confidence: 99%
“…The inter-relationship between these two parameters governs the activation energy for crystallization, DE. Following the isokinetic method of Augis-Bennet, DE values were evaluated [56][57][58][59]: where T 0 is the initial reference temperature from the melt state, T p the crystallization peak temperature, R g the universal gas constant (R g = 8.314 J mol -1 K -1 ), and R is the cooling rate. The activation energy was calculated from the slopes, of the plots, Fig.…”
Section: Activation Energy Of Crystallizationmentioning
confidence: 99%
“…Furthermore, the PBT/MWNT nanocomposites have higher T p than the neat PBT at all cooling rates. Oburoğlu et al studied the crystallization behavior of PBT and PBT‐based composites including 5 wt % of different types of filler, halloysite (tubular alumina‐silicate as 1D filler), organo‐montmorillonite (organically modified layered alumina‐silicate as 2D filler), and calcite (spherical CaCO 3 particles as 3D filler). They found that 1D and 3D fillers acted as efficient nucleating agent and thus enhanced the crystallization rate of PBT, which was contributed to geometrically less efficient restriction effect of such fillers on the polymer chains, but 2D filler had considerably high surface area which could reduce the crystallization rate of PBT.…”
Section: Resultsmentioning
confidence: 99%
“…is important for the crystallization behavior of polymers (Oburoğlu et al, 2012b). On the other hand, it was found that OMMT reduced the melt-crystallization rate of PBT.…”
Section: Content Of Nanofillermentioning
confidence: 99%
“…It is PBT nanocomposites systems important to understand relationships between processing conditions, crystallization behaviors, structures, morphological developments, and final properties to obtain polymer products that meet industry requirements (Zhang et al, 2010;Shukla et al, 2011;Oburoğlu et al, 2012b). It is PBT nanocomposites systems important to understand relationships between processing conditions, crystallization behaviors, structures, morphological developments, and final properties to obtain polymer products that meet industry requirements (Zhang et al, 2010;Shukla et al, 2011;Oburoğlu et al, 2012b).…”
Section: Crystallization Behaviorsmentioning
confidence: 99%